Simple proofs of certain inequalities with logarithmic coefficients of univalent functions - Obradović, M.; Tuneski, N. (Oles Honchar Dnipropetrovsk National University, 2024)
In this paper, we give simple proofs for the bounds (some of them sharp) of the difference of the moduli of the second and the first logarithmic coefficient for the general class of univalent functions and for the class of convex univalent functions.